ChemInform Abstract: Stereoselective Total Synthesis and Structural Elucidation of (‐)‐Indoxamycins A—F. Issue 19 (May 2015) - He, Chi; Zhu, Chenlong; Wang, Bingnan; Ding, Hanfeng
Abstract None of the compounds show significant cytotoxic activities against HT‐29 and A‐549 tumor cell lines.